Therapeutic communication in nursing students: A cross-sectional study of personal, educational, and contextual factors - Jaime Carballedo-Pulido; Mariona Farrés-Tarafa; Juan Roldán-Merino; Bárbara Hurtado-Pardos; Marta Berenguer-Poblet; Manuel Tomás-Jiménez; Carla Otero-Arús; Marta Domínguez-del-Campo; Ivette Fernández-Gibert; Susana Santos-Ruiz (PLoS ONE, 2026)
Background Therapeutic communication is a key competency in nursing education and a central component of person-centred care. However, evidence regarding its association with personal, educational, and contextual factors among nursing students remains heterogeneous. Objective To describe therapeutic communication scores in nursing students and to examine their association with personal, educational, and contextual variables using the Therapeutic Communication Scale in Nursing Students. Methods A cross-sectional study was conducted among second-, third-, and fourth-year undergraduate nursing students at a Spanish university. Participants completed a questionnaire including sociodemographic and academic variables, self-perceived communication ability, factors related to stress and the clinical practice context, and the Therapeutic Communication Scale in Nursing Students, which provides a total score and two dimensions: Relation Building and Problem Solving. Descriptive statistics were calculated, and bivariate analyses were performed using non-parametric tests. Results A total of 450 students participated. Mean scores indicated a generally high level of therapeutic communication. Female students obtained significantly higher scores than male students in both dimensions and in the total scale score. No significant differences were observed according to academic shift, employment status, volunteering experience, or academic stress level. Higher self-perceived communication ability and greater motivation towards nursing studies were associated with higher therapeutic communication scores. In addition, students who reported frequent use of communicative behaviours such as active listening, verbal empathy, and open-ended questions showed significantly higher scores. Perceived support from clinical tutors and clinical accompaniment was not associated with communication scores, whereas a favourable clinical climate was associated with slightly higher total scores. Conclusions Therapeutic communication in nursing students appears to be more strongly associated with self-perceived competence, academic motivation, and specific communicative behaviours than with sociodemographic characteristics or stress levels. These findings highlight the importance of strengthening training in concrete communication skills during undergraduate nursing education.